2006
DOI: 10.1111/j.1365-2559.2006.02466.x
|View full text |Cite
|
Sign up to set email alerts
|

Advanced colorectal polyps with the molecular and morphological features of serrated polyps and adenomas: concept of a ‘fusion’ pathway to colorectal cancer

Abstract: Advanced colorectal polyps with the molecular and morphological features of serrated polyps and adenomas: concept of a 'fusion' pathway to colorectal cancer Aim: To establish and explain the pattern of molecular signatures across colorectal polyps. Methods and results: Thirty-two sessile serrated adenomas (SSA), 10 mixed polyps (MP), 15 traditional serrated adenomas (SA), 49 hyperplastic polyps (HP) and 84 adenomas were assessed for mutation of KRAS and BRAF and aberrant expression of p53. The findings were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
209
5
6

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(248 citation statements)
references
References 60 publications
28
209
5
6
Order By: Relevance
“…40 These canonical pathways are largely linear in nature, and are likely to serve as the foundation of colorectal carcinoma development in the majority of instances. In 2006, Jass et al 41 proposed a 'fusion pathway', which combined elements from the canonical pathways. It was suggested that other mutational alterations, such as the inactivation of MGMT, may combine with KRAS and TP53 mutations to produce malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…40 These canonical pathways are largely linear in nature, and are likely to serve as the foundation of colorectal carcinoma development in the majority of instances. In 2006, Jass et al 41 proposed a 'fusion pathway', which combined elements from the canonical pathways. It was suggested that other mutational alterations, such as the inactivation of MGMT, may combine with KRAS and TP53 mutations to produce malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Briefly, real-time PCR was performed using allelespecific primers designed to selectively amplify the wild-type (T1796) and mutant (A1796) BRAF alleles. The primer sequences were as follows: V, 5 0 -GTGATTTTGGTC TAGC TACtGT; E, 5 0 -CGCGG CCGGCCGCGGCGGTGATTTTGGTCTA GCTACcGA; and AS, 5 0 -TAGCCTCAATTCTTACCAT CCAC.…”
Section: Braf and Kras Mutation Analysismentioning
confidence: 99%
“…4,[6][7][8][9][10][11][12][13] In contrast, KRAS mutations have shown to be rare in SSA/Ps (0-8%), but more common in conventional tubular adenomas (5-37%). 4,6,10,11,13 In our study, BRAF mutations were frequent (82%), whereas KRAS mutation was not detected in SSA/ Ps, with clearly contrasting results for tubular adenomas (BRAF mutation, 0%, KRAS mutation, 26%). Similar trends were found in SSA/Ps with high-grade dysplasia vs tubular adenomas with high-grade dysplasia and SSA/Ps with submucosal carcinoma vs tubular adenomas with submucosal carcinoma.…”
Section: Modern Pathology (2015) 28 146-158mentioning
confidence: 99%
“…shown associations of SSA/P and those with dysplasia or carcinoma with methylation or loss of protein expression for DNA repair genes, ie, MLH1, 1,4,6-9 a CpG island methylator phenotype, 3,4,6,8 BRAF mutations, 3,4,[6][7][8][9][10][11][12][13][14] and a lack of genetic alterations in CTNNB1 (the gene coding for b-catenin protein). 14 This pathway is thought to be distinct from the conventional adenoma-carcinoma pathway, where adenomas progress to invasive colorectal carcinomas through the influence of a series of genetic alterations including adenomatous polyposis coli (APC) and KRAS mutations.…”
mentioning
confidence: 99%
See 1 more Smart Citation